Pengaruh Pemberian Cookies Bunite terhadap Kadar Gula Darah Sewaktu pada Penderita DM Tipe 2 - Muzakar, Muzakar; Dewi, Arifah Rahma; Listrianah, Listrianah (Jurnal Kesehatan, 2021)
The prevalence of DM in Indonesia in 2018 was 2.0% and in South Sumatra was 20,7%. Non-pharmacological management of DM is by giving "cookies bunite". Research objectives are to find out the effect of giving "cookies bunite" to blood sugar levels in patients with type 2 diabetes. The type of research used was quasi-experimental with the research design "The type of research is a quasi-experiment with a pretest and posttest control group design". This research was conducted from September to March 2021 at the Public Health Center Social in Palembang. Samples were patients with type 2 Diabetes Mellitus who were selected by purposive sampling with inclusion criteria: blood sugar levels 200mg/dl and age 40 years, male and female. The number of samples in the treatment and comparison groups was 30 respondents each. Data were collected by purposive sampling technique and selected according to the criteria. Data analysis used paired sample test and independent t-test with the difference in the average blood glucose levels of the treatment group 45, 27 mg/dl (p-value=0,00) and the experimental group. comparison 18,9mg/dl (p-value=0,00). The difference in decreasing blood glucose levels between the intervention group was mg/dl and the comparison group was 26.37 mg/dl. The result of the independent sample test statistic is p-value=0,013. There was an effect of giving "cookies bunite" on blood glucose levels in patients with type 2 Diabetes Mellitus with the average difference in the treatment group being greater than in the control group. There is an effect of giving "cookies bunite" to decrease blood glucose levels in patients with type 2 Diabetes Mellitus.Â